Nanosecond lifetime measurements of Iπ=9/2- intrinsic excited states and low-lying B(E1) strengths in 183Re using combined HPGe-LaBr3 coincidence spectroscopy. (August 2017) - Gurgi, L.A.; Regan, P.H.; Daniel, T.; Podolyák, Zs.; Bruce, A.M.; Mason, P.J.R; Mǎrginean, N.; Mǎrginean, R.; Werner, V.; Alharbi, T.; Alkhomashi, N.; Bajoga, A.D.; et al.
Abstract: This paper presents precision measurements of electromagnetic decay probabilities associated with electric dipole transitions in the prolate-deformed nucleus 183 Re. The nucleus of interest was formed using the fusion evaporation reaction 180 Hf( 7 Li, 4n) 183 Re at a beam energy of 30 MeV at the tandem accelerator at the HH-IFIN Institute, Bucharest Romania. Coincident decay gamma rays from near-yrast cascades were detected using the combined HPGe-LaBr3 detector array ROSPHERE. The time differences between cascade gamma rays were measured using the LaBr3 detectors to determine the half-lives of the two lowest lying spin-parity 9/2 - states at excitation energies of 496 and 617 keV to be 5.65(5) and 2.08(3) ns respectively. The deduced E1 transition rates from these two states are discussed in terms of the K-hindrance between the low-lying structures in this prolate-deformed nucleus. Highlights: Measurement made of EM transition probabilities from low-lying I π =9/2 - states in 183 Re. ROSPHERE gamma-ray array used to isolating discrete gamma-ray cascades. Derived the reduced hindrances of E1 transitions in 183 Re related to K-quantum number conservation.